2009
DOI: 10.1158/1535-7163.mct-08-1147
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid receptor 1 is a potential drug target for treatment of translocation-positive rhabdomyosarcoma

Abstract: Gene expression profiling has revealed that the gene coding for cannabinoid receptor 1 (CB1) is highly up-regulated in rhabdomyosarcoma biopsies bearing the typical chromosomal translocations PAX3/FKHR or PAX7/FKHR. Because cannabinoid receptor agonists are capable of reducing proliferation and inducing apoptosis in diverse cancer cells such as glioma, breast cancer, and melanoma, we evaluated whether CB1 is a potential drug target in rhabdomyosarcoma. Our study shows that treatment with the cannabinoid recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 36 publications
2
24
0
Order By: Relevance
“…As seen in Fig. 2C Previously, it has been reported that treatment with the CNR1 agonist Met-F-AEA can induce apoptosis in ARMS cell lines (32). Treatment with either 3 or 30 mmol/L Met-F-AEA for 24 hours failed to induce any increase in apoptosis over that These results show that although CNR1 is grossly upregulated by PAX3-FOXO1 it does not play an appreciable role in enhanced proliferation, inhibited differentiation, or enhanced transformation seen with PAX3-FOXO1 expression in primary myoblasts.…”
Section: Cnr1 Upregulation Does Not Contribute To Proliferation Diffmentioning
confidence: 64%
See 1 more Smart Citation
“…As seen in Fig. 2C Previously, it has been reported that treatment with the CNR1 agonist Met-F-AEA can induce apoptosis in ARMS cell lines (32). Treatment with either 3 or 30 mmol/L Met-F-AEA for 24 hours failed to induce any increase in apoptosis over that These results show that although CNR1 is grossly upregulated by PAX3-FOXO1 it does not play an appreciable role in enhanced proliferation, inhibited differentiation, or enhanced transformation seen with PAX3-FOXO1 expression in primary myoblasts.…”
Section: Cnr1 Upregulation Does Not Contribute To Proliferation Diffmentioning
confidence: 64%
“…Recently, Oesch and colleagues (32) reported that treatment of ARMS cell lines, RH4 in particular, with Cnr1 agonists induced apoptosis. We did not find induction of apoptosis in RH4 with treatment of MET-F-AEA [ Fig.…”
Section: Discussionmentioning
confidence: 99%
“…inhibition of cnr1 with increased concentrations of aM28, an antagonistic inhibitor did not impair cell viability of the rMS cells (rh30 and rD) at concentrations below 40 µM (unpublished own data). However, agonists of cnr1 reduced rMS cell proliferation (23).…”
Section: Discussionmentioning
confidence: 97%
“…RAS Mutations [12,13] SHH Activation [14] IGF2 Loss of imprinting [15,16] EGFR Overexpression [17,18] translocation-positive RMS PAX/FKHR Translocation [11,19] NMYC Amplification [20] FGFR4 Mutations [21,22] CB1 - [23] IL4R…”
Section: Translocation-negative Rmsmentioning
confidence: 99%